Olfactory Neuroblastoma with Intracranial Extension - Andry Nurwahyu Putra Romadhani; Iqbal Imanuddin; Teddy Tejomukti; Yasuhiro Watanabe; Takenobu Murakami; Yuki Tajiri (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: Olfactory Neuroblastoma (ONB), so called esthesioneuroblastoma, is a rare malignant tumor of the sinonasal tract. ONB represents 6.3% of all sinonasal tract malignancies, with a prevalence of 0.4 cases per million population. These tumors are slow-growing and there may be intracranial extension of the tumor. Nasal obstruction, anosmia, recurrent epistaxis and pain are typical early manifestations. Imaging studies are essential in determining tumor extension and surgical planning of ONB. Endonasal biopsy is required to confirm the diagnosis of ONB. The case provides a basis for discussion of ONB and highlights the possibility of extension of this tumor. Case: A 45-year-old male presented with a generalized clonic seizure, conjugate eye deviation, and pre-seizure headache. Post-seizure, the patient was unconscious and incontinent, later appearing conscious but confused. The patient had a history of seizures at home and in the ER, along with occasional headaches over the past year. The patient described nasal congestion, decreased smell, and recurrent nosebleeds, having undergone ethmoidectomy in 2020 for papilloma. Discussion: The patient experienced symptoms of seizures, headache, and nasal disturbances. Olfactory neuroblastoma (ONB) tumor was detected after comprehensive examination. Treatment involves multimodal therapy, including surgery, chemotherapy, and radiotherapy, with prognosis depending on tumor stage and grade. Conclusion: Early diagnosis of ONB is necessary to prevent further tumor progression. Intracranial extension of the ONB should be carefully investigated. Imaging as well as histopathological and immunohistochemical examinations are very helpful in identifying the location, metastasis and degree of malignancy of the tumor.